1995
DOI: 10.1017/s0022215100130877
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement and number of intralaryngeal ganglia and ganglionic neurons: comparative study of five species of mammals

Abstract: The arrangement and number of intralaryngeal ganglia and their neurons in five mammals (dog, rat, guinea pig, rabbit and cat) were examined morphologically. Intralaryngeal ganglions were situated mainly in branches of the internal branch of superior laryngeal nerve (Int-SLN), dorsal and/or dorsolateral to the posterior cricoarytenoid muscle, and around the inferior laryngeal nerve in dogs, rats, guinea pigs and cats, but they were identified at the branching out point ofthe Int-SLN exclusively in rabbits. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Some authors suggested that they represent paraganglia consisting of cells having chemoceptive function (Watzka 1963, Kleinsasser 1964). On the other hand, investigations performed in animals, rats (Luts et al 1990, Krekel et al1990, Shimazaki et al 1995, Hisa et al 1996b, Robertson et al 1998, Nakanishi et al 1999, Koike et al 2004, Okano et al 2006, cats (Tsuda et al 1992, Tanaka et al 1993a, Yoshida et al 1993, Shimazaki et al 1995, dogs (Shimazaki et al 1995, Hisa et al 1996a, Yamamoto et al 1998, guinea-pigs (Shimazaki et al 1995), rabbits (Shimazaki et al 1995) and horses (Corcoran et al 1999) with the use of histo-and immunohistochemical methods have provided strong evidence that these cells are neurons containing some biologically active substances. Furthermore, considering the chemical coding of local laryngeal neurons it is generally assumed that they are parasympathetic nerve cells as they express cholinergic markers (choline acetyltransferase, ChAT, or acetylcholinesterase, AChE) and some other substances typical of cholinergic-parasympathetic nerve structures, such as vasoactive intestinal polypeptide (VIP) or nitrergic markers (nitric oxide synthase, NOS or NADPH-diaphorase, NADPHd).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested that they represent paraganglia consisting of cells having chemoceptive function (Watzka 1963, Kleinsasser 1964). On the other hand, investigations performed in animals, rats (Luts et al 1990, Krekel et al1990, Shimazaki et al 1995, Hisa et al 1996b, Robertson et al 1998, Nakanishi et al 1999, Koike et al 2004, Okano et al 2006, cats (Tsuda et al 1992, Tanaka et al 1993a, Yoshida et al 1993, Shimazaki et al 1995, dogs (Shimazaki et al 1995, Hisa et al 1996a, Yamamoto et al 1998, guinea-pigs (Shimazaki et al 1995), rabbits (Shimazaki et al 1995) and horses (Corcoran et al 1999) with the use of histo-and immunohistochemical methods have provided strong evidence that these cells are neurons containing some biologically active substances. Furthermore, considering the chemical coding of local laryngeal neurons it is generally assumed that they are parasympathetic nerve cells as they express cholinergic markers (choline acetyltransferase, ChAT, or acetylcholinesterase, AChE) and some other substances typical of cholinergic-parasympathetic nerve structures, such as vasoactive intestinal polypeptide (VIP) or nitrergic markers (nitric oxide synthase, NOS or NADPH-diaphorase, NADPHd).…”
Section: Introductionmentioning
confidence: 99%